2021
DOI: 10.1016/j.ajhg.2021.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Shifting landscapes of human MTHFR missense-variant effects

Abstract: Most rare clinical missense variants cannot currently be classified as pathogenic or benign. Deficiency in human 5,10-methylenetetrahydrofolate reductase (MTHFR), the most common inherited disorder of folate metabolism, is caused primarily by rare missense variants. Further complicating variant interpretation, variant impacts often depend on environment. An important example of this phenomenon is the MTHFR variant p.Ala222Val (c.665C>T), which is carried by half of all humans and has a phenotypic impact that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 58 publications
2
40
0
1
Order By: Relevance
“…This C136T variant was in weak linkage disequilibrium (LD) with the C677T variant ( r 2 = 0.014). A previous enzyme kinetics experiment has shown that the arginine to tryptophan substitution at C136T led to a reduced enzymatic activity of MTHFR , which provided direct evidence for a functional role of this variant, consistent with our observation of the presence of multiple causal mutations at this locus ( Tan et al, 2021 ; Weile et al, 2021 ). A haplotype analysis further showed that these two alleles (677T and 136T) together affect tHCY in a compound heterozygote manner ( Figure 4 ).…”
Section: Resultssupporting
confidence: 92%
“…This C136T variant was in weak linkage disequilibrium (LD) with the C677T variant ( r 2 = 0.014). A previous enzyme kinetics experiment has shown that the arginine to tryptophan substitution at C136T led to a reduced enzymatic activity of MTHFR , which provided direct evidence for a functional role of this variant, consistent with our observation of the presence of multiple causal mutations at this locus ( Tan et al, 2021 ; Weile et al, 2021 ). A haplotype analysis further showed that these two alleles (677T and 136T) together affect tHCY in a compound heterozygote manner ( Figure 4 ).…”
Section: Resultssupporting
confidence: 92%
“…It has become possible to experimentally assess the functional impact of nearly all possible missense variants for a target protein, yielding “deep mutational scans” or “variant effect maps.” 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 However, the MaveDB 14 resource currently contains variant effect maps for fewer than 1% of the ∼4,000 human disease-associated proteins, and a high-quality fully-comprehensive experimental atlas of functional missense variation could be decades away.…”
Section: Introductionmentioning
confidence: 99%
“…Rare variation is reported in gnomAD for many junctin encoded amino acids residues outside of the KEKE motifs, thus making it critical to define which changes are likely pathogenic and which are not. An approach that combines variant scanning 44 with functional validation, if a suitable high throughput assay can be established, is an attractive strategy for evaluating the potential pathogenicity of other junctin variants.…”
Section: Discussionmentioning
confidence: 99%